Amperometric Detection of Nitrite on Glassy Carbon Electrode Modified with Cobalt Nitroprusside - Sabzi,R.E. (2007)
The glassy carbon electrode (GCE) modified with cobalt nitroprusside (CoNP) was prepared by electrochemical method. The CoNP modified electrode (ME) prepared electrochemically on a GCE in two-step. The electrochemical behavior of the modified electrode was studied by cyclic voltammetric technique. The cyclic voltammogram of CoNP showed a redox couple with formal potential [E0 =(Epa+Epc)/2] of 500 mV vs. SCE. The electrocatalytic oxidation of nitrite was studied on the CoNP modified glassy carbon electrode. The CoNP films on the glassy carbon electrode show an excellent electrocatalytic activity toward the oxidation of nitrite in 0.5 mol L-1 KNO3. Hydrodynamic amperometry was used to the detection of nitrite with CoNP. The linear detection limit of the CoNP elctrode for NO2- was from 20×10-6 to 220×10-4 mol L-1 and the detection limit was 10×10-6 mol L-1 (S/N=3).